2023
DOI: 10.1021/acsaem.3c01365
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Layer-Protected CoP/Carbon Nanosheets as Highly Durable Bifunctional Electrocatalysts for Rechargeable Zinc–Air Batteries

Abstract: The commercialization of rechargeable Zn−air batteries (ZABs) relies heavily on the development of costeffective and highly durable bifunctional electrocatalysts that can promote both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Transition-metal phosphides-based carbon (TMPs/C) composites have recently been acknowledged as highly efficient bifunctional catalysts, yet the successful construction of TMPs/C still remains a formidable challenge. Here, we report a carbon dots (CDs)-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…voltage than the equivalent with the commercialized catalyst (Figure 20d). [102] Analogous to transition metal-based electrocatalysts, layered double hydroxide (LDH) are also perceived as promising catalysts in improving the OER by reason of their large specific surface area, unique 2D lamellar structures, and adjustable chemical properties, whereas the finite numbers of active sites with an inferior catalytic activity in LDH hamper their electrocatalytic ORR activity. [103][104][105] According to the investigations by predecessors, preparing ultrathin LDH nanosheets and LDH integrated CDs are regarded as advantageous methods to improve the electrocatalytic OER activity through exposing more active sites and modulating the surface electronic structure.…”
Section: Cds Used In Electrocatalystsmentioning
confidence: 99%
“…voltage than the equivalent with the commercialized catalyst (Figure 20d). [102] Analogous to transition metal-based electrocatalysts, layered double hydroxide (LDH) are also perceived as promising catalysts in improving the OER by reason of their large specific surface area, unique 2D lamellar structures, and adjustable chemical properties, whereas the finite numbers of active sites with an inferior catalytic activity in LDH hamper their electrocatalytic ORR activity. [103][104][105] According to the investigations by predecessors, preparing ultrathin LDH nanosheets and LDH integrated CDs are regarded as advantageous methods to improve the electrocatalytic OER activity through exposing more active sites and modulating the surface electronic structure.…”
Section: Cds Used In Electrocatalystsmentioning
confidence: 99%
“…16 Therefore, the strategy of using carbon materials to modify the CoP is an effective method to improve the OER performance of the CoP. 17 For instance, Wu et al reported a series of carbon-coated cobalt-based materials. Among them, carbon-encapsulated CoP nanowires (CoP/C NWs) exhibited an outperform OER performance, whose overpotential for OER is just 230 mV.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal phosphides (TMPs), especially cobalt-based phosphides (CoP), have shown great potential as OER catalysts due to their large earth abundance, outstanding electrical conductivity, and excellent catalytic stability. , However, further practical application of CoP is significantly hindered because of its large overpotential and deficient active sites. , On account of the powerful synergistic effect between carbon materials and active materials, such as (CoP), these composite materials can increase the surface area of catalysts to obtain abundant active sites and then promote charge transfer . Therefore, the strategy of using carbon materials to modify the CoP is an effective method to improve the OER performance of the CoP . For instance, Wu et al reported a series of carbon-coated cobalt-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Among them, CoP have garnered significant research attention in this research field, owing to its metalloid characteristic property and remarkable electronic conductivity. [12] To optimize the morphology and composition of nanocatalysts, Wu et al fabricated a composite electrocatalyst consisting of highly dispersed Co/CoP heterojunction embedded within a hierarchically porous carbon matrix, which exhibited exceptional performance for hydrogen and oxygen evolution. [13] Though more and more researchers focused on the preparation of high-activity cobalt-based phosphides in recent years, it is still a challenge to synthesize uniform CoP nanocatalyst with well-defined morphology and long-term durability.…”
Section: Introductionmentioning
confidence: 99%